2021
DOI: 10.1016/j.celrep.2021.108929
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of APC/C release from spindle assembly checkpoint inhibition by APC/C SUMOylation

Abstract: Highlights d APC/C SUMOylation causes substantial rearrangement of the WHB domain of the APC2 subunit d The repositioned WHB domain prevents robust binding of the MCC to the APC/C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…One perspective is that APC/C-mediated ubiquitination drives the disassembly of MAD2 and BUBR1, and then UBCH10 mediates the inactivation of the SAC 52 . In addition, SUMOylation of the APC/C attenuates MCC-mediated suppression of APC/C CDC20 activity, which permits the catalytic activity of the APC/C before the SAC is turned off 72 . As a subunit of APC/C, APC15 catalyses the disassembly/degradation of APC/C-bound MCC 73 .…”
Section: Discussionmentioning
confidence: 99%
“…One perspective is that APC/C-mediated ubiquitination drives the disassembly of MAD2 and BUBR1, and then UBCH10 mediates the inactivation of the SAC 52 . In addition, SUMOylation of the APC/C attenuates MCC-mediated suppression of APC/C CDC20 activity, which permits the catalytic activity of the APC/C before the SAC is turned off 72 . As a subunit of APC/C, APC15 catalyses the disassembly/degradation of APC/C-bound MCC 73 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mass spectrometry analysis of APC/C showed a lactate‐dependent elevation of SUMO2/3 conjunctions. Previous studies have shown that SUMOylation of APC4 on residues K772 and K798 results in a substantial rearrangement of the WHB domain in APC2, facilitating the binding of UBE2C to APC/C for an efficient APC/C activation 3,4 . To further investigate the role of APC4 SUMOylation in lactate‐mediated UBE2C–APC/C interactions, Liu et al constructed APC4 K772/798R cells in which APC4 SUMOylation is abrogated.…”
Section: Figurementioning
confidence: 99%
“…Previous studies have shown that SUMOylation of APC4 on residues K772 and K798 results in a substantial rearrangement of the WHB domain in APC2, facilitating the binding of UBE2C to APC/C for an efficient APC/C activation. 3,4 To further investigate the role of APC4 SUMOylation in lactate-mediated UBE2C-APC/C interactions, Liu et al constructed APC4 K772/798R cells in which APC4 SUMOylation is abrogated. They found that the lactate-mediated interaction between UBE2C and APC/C was completely lost in these cells.…”
mentioning
confidence: 99%
“…SUMOylation has been known to affect mitosis in various ways (Dasso, 2008;Dawlaty et al, 2008;Eifler et al, 2018;Eifler and Vertegaal, 2015;Johansson et al, 2021;Liu et al, 2023;Ptak et al, 2021;Sridharan and Azuma, 2016;Yatskevich et al, 2021). During a normal mitosis, replicated sister chromatids segregate and move to the opposite poles of the mitotic spindle during anaphase, which is followed by spindle disassembly and cytokinesis that divides the daughter cells.…”
Section: Introductionmentioning
confidence: 99%